Effectiveness of Flexible Learning Spaces on the Performance in English of Grade Six Pupils - Romero, Camille (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study aimed to determine the effectiveness of flexible learning spaces in teaching English to Grade Six pupils at Alas-asin Elementary School, Tanay District, Division of Rizal during the School Year 2025–2026. The respondents were thirty-two (32) Grade Six pupils described in terms of age, sex, sibling position, number of children in the family, parents’ educational attainment, parents’ occupation, and monthly family income. Using an experimental research method with a single-group pretest-posttest design, the pupils’ English performance was measured before and after exposure to flexible learning spaces. Findings revealed that the pupils’ English performance improved from Fairly Satisfactory to Satisfactory after the intervention. A significant difference was observed in overall performance before and after exposure, with sex identified as a contributing factor, while other demographic variables showed no significant effect.It was concluded that flexible learning spaces effectively enhance English performance among Grade Six pupils, with sex influencing the degree of improvement. Based on these findings, it is recommended that school administrators provide professional development for teachers on flexible learning space utilization, implement equitable access policies, design task-based and collaborative learning activities, adopt performance-based assessments, and educate parents on supporting flexible learning at home. An action plan for effective implementation of flexible learning spaces is also proposed. Future studies may explore other variables to further validate the approach.